Vice patrol: cops, courts, and the struggle over urban gay life before stonewall - Lvovsky, Anna (De Gruyter eBook-Paket Rechtswissenschaften, 2021)
Frontmatter -- CONTENTS -- List of Illustrations -- INTRODUCTION -- ONE / When Anyone Can Tell -- TWO / Expert Witnesses on Trial -- THREE / Plainclothes Decoys and the Limits of Criminal Justice -- FOUR / The Rise of Ethnographic Policing -- FIVE / Peepholes and Perverts -- SIX / The Popular Press and the Gay World -- EPILOGUE -- Acknowledgments -- List of Abbreviations -- Notes -- Index